2016
DOI: 10.1097/md.0000000000004850
|View full text |Cite
|
Sign up to set email alerts
|

HIV and cancer registry linkage identifies a substantial burden of cancers in persons with HIV in India

Abstract: We utilized computerized record-linkage methods to link HIV and cancer databases with limited unique identifiers in Pune, India, to determine feasibility of linkage and obtain preliminary estimates of cancer risk in persons living with HIV (PLHIV) as compared with the general population.Records of 32,575 PLHIV were linked to 31,754 Pune Cancer Registry records (1996–2008) using a probabilistic-matching algorithm. Cancer risk was estimated by calculating standardized incidence ratios (SIRs) in the early (4–27 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
0
12
1
1
Order By: Relevance
“…For example, breast cancer incidence in Taiwan, occurs at a lower median age compared to Western countries, with different molecular subtypes 7 . In a linkage study conducted in India, no cases of KS were reported, which was in contrast to reported findings from the African region 8 . The European COHERE cohort found a significant risk for AIDS-related NHL among male-to-male sex (MSM) and older age groups 9 , however the risk in South African women was reportedly higher than those in Europe 10 .…”
Section: Introductioncontrasting
confidence: 83%
“…For example, breast cancer incidence in Taiwan, occurs at a lower median age compared to Western countries, with different molecular subtypes 7 . In a linkage study conducted in India, no cases of KS were reported, which was in contrast to reported findings from the African region 8 . The European COHERE cohort found a significant risk for AIDS-related NHL among male-to-male sex (MSM) and older age groups 9 , however the risk in South African women was reportedly higher than those in Europe 10 .…”
Section: Introductioncontrasting
confidence: 83%
“…The high burden of anal cancer in PLWHIV is not limited to developed countries. In emerging economies like Brazil and India, high rates of anal cancer in those with HIV/AIDS have also been reported in recent years [24,25].…”
Section: Discussionmentioning
confidence: 98%
“…The rapid expansion of ART and the promulgation of the 90-90-90 treatment targets have renewed the focus on case reporting, linked to patient monitoring systems, by WHO and UNAIDS. In settings where unique identifiers are available, HIV case report systems can be crossed with registries where they exist to link associated conditions; currently, cancer registries are the most prevalent [56]. Every effort should be made to protect patient privacy and ensure confidentiality as individual systems grow to collect more data elements and are linked to other systems.…”
Section: Case-based Reporting and Population-level Patient Monitoringmentioning
confidence: 99%